Revenge of the living dummy - "Stine, R.L" (Scholastic Inc., New York, 2008 New York, 2008)
Britney battles against her cousin's new ventriloquist dummy and discovers a frightening secret in a new amusement park called HorrorLand
Keywords: Horror stories